NifB and NifEN protein levels are regulated by ClpX2 under nitrogen fixation conditions in Azotobacter vinelandii - Martínez Noël, Giselle María Astrid (2011)
The major part of biological nitrogen fixation is catalysed by the molybdenum nitrogenase that carries at its active site the iron and molybdenum cofactor (FeMo-co). The nitrogen fixation (nif) genes required for the biosynthesis of FeMo-co are derepressed in the absence of a source of fixed nitrogen. The nifB gene product is remarkable because it assembles NifB-co, a complex cluster proposed to comprise a [6Fe-9S-X] cluster, from simpler [Fe-S] clusters common to other metabolic pathways. NifB-co is a common intermediate of the biosyntheses of the cofactors present in the molybdenum, vanadium and iron nitrogenases. In this work, the expression of the Azotobacter vinelandii nifB gene was uncoupled from its natural nif regulation to show that NifB protein levels are lower in cells growing diazotrophically than in cells growing at the expense of ammonium. A. vinelandii carries a duplicated copy of the ATPase component of the ubiquitous ClpXP protease (ClpX2), which is induced under nitrogen fixing conditions. Inactivation of clpX2 resulted in the accumulation of NifB and NifEN and a defect in diazotrophic growth, especially when iron was in short supply. Mutations in nifE, nifN and nifX or in nifA also affected NifB accumulation, suggesting that NifB susceptibility to degradation might vary during its catalytic cycle.